2017
DOI: 10.1002/met.1618
|View full text |Cite
|
Sign up to set email alerts
|

An example of synergistic coupling of upper‐ and lower‐level jets associated with flash flooding

Abstract: A brief case study is provided of a striking example of vertical and horizontal jet coupling associated with the upper jet level as well as upper-and lower-level jet coupling; these jet interactions also supported the development of elevated convection and led to flash flooding. The case constitutes a faithful, real-world verification of what has been suggested in idealized conceptual models by several investigators for similar situations of elevated convection with excessive precipitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Elevated storm systems and surface-based thunderstorms both can produce heavy precipitation (Kastman et al, 2017b). The heavy precipitation from surface-based systems is mainly due to the slow movement of the storm system.…”
Section: Liftingmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated storm systems and surface-based thunderstorms both can produce heavy precipitation (Kastman et al, 2017b). The heavy precipitation from surface-based systems is mainly due to the slow movement of the storm system.…”
Section: Liftingmentioning
confidence: 99%
“…Ducrocq et al (2008) have shown that downward motion occurs immediately above the surface cold pools with significant downdrafts originating in the mid-troposphere. A mesoscale cold front (meso-low) (Peters and Schumacher, 2015) and a mesoscale cyclonic/convective vortex (Dodla and Ratna, 2010;Kozaric and Ivančan-Picek, 2006;Ullah and Shouting, 2013) as well the interaction between a mesoscale convective vortex (Schumacher and Johnson, 2008) (or other mid-level circulations like cut-off lows; Schumacher and Johnson (2009)) or a front (Jeong et al, 2016b;Konrad, 1997) and a low-level jet also can contribute to the convergence and uplift as well as the destabilisation of low-level air (Kastman et al, 2017b;Peters and Schumacher, 2015;Schumacher and Johnson, 2009). The mid-level positive potential vorticity anomaly as associated with a mesoscale convective vortex originated from a decaying mesoscale convective vortex or from a cutoff low will force ascent in an environment with ambient vertical shear (Schumacher et al, 2013;Schumacher and Johnson, 2009) and resembles the large-scale potential vorticity anomaly and its large-scale ascent as mentioned before.…”
Section: Liftingmentioning
confidence: 99%
“…Several synoptic-and mesoscale factors conspired to produce this unique episode, including the interaction of two separate UL jet streaks. While coupled upper-level jets are primarily cool-season phenomena, they can occur during the warmer months, as evidenced by a case of flash flooding in July 2006 studied by Kastman et al [23], in which upper-level jet streak interaction was partly responsible for the elevated convection that led to the excessive precipitation.…”
Section: Advances In Meteorologymentioning
confidence: 99%
“…Elevated thunderstorm complexes pose numerous threats and are well established as producers of heavy rainfall [1][2][3][4], flash flooding [3][4][5], and cloud-to-ground lightning flashes [4,6,7]. Furthermore, these elevated complexes are suspected of disrupting synoptic boundary location and movement [8,9] as cold pools from convection interact with surface boundaries.…”
Section: Introductionmentioning
confidence: 99%